EFFECT OF BIOCHEMICAL PARAMETERS ON MALARIA INFECTED PATIENTS IN GENERAL HOSPITAL BILLIRI, GOMBE STATE NIGERIA - J, PHILIMON; G, CHESSED; PUKUMA,; E, ABBA; Y.U, AMINA; M, ISHAKU; Y, LAMOGO; A., JEMIMAH,; A, SARKI; A.A, MUHAMMAD; S, SHUAIBU; A, FATAI, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
This study was carried out to determine the impact of malaria parasite infection caused by Plasmodium falciparum on some biochemical parameters. One hundred and five (105) malaria parasite positive male and female subjects and fifty (50) apparently healthy subjects were recruited for this study. Malaria Parasite diagnosis was done by Microscopic Examination of Thick and Thin Stained Blood Films. Age range 15-25 had the highest prevalent rate of 17.14% for males and 14.29% for females while the age range 55-60 had the least prevalent rate of 0.95% for both male and female. when control values were compared with the mean values obtained from the biochemical analysis of Plasmodium falciparum parasitaemia subject samples, it was significantly lower for glucose (p=0.04), ALT (p=0.00), AST (p=0.00), ALP (p=0.00), total protein (p=0.01), Globulin (p=0.02) and Creatinine (p=0.04). Total cholesterol (p=0.12), Triglyceride (p=0.06), Albumin (p=0.49) and Urea (p=0.15) were statistically not significant for malaria parasitaemia subject samples. Glucose, Total cholesterol, Liver enzymes, creatinine changes were seen involved in malaria infection caused by Plasmodium falciparum. The prevention of malarial infection is still the most valid method of preventing these conditions and early diagnosis and treatment are the measures likely to decrease malarial complications commonly determined by changes in these biochemical parameters.